ChemInform Abstract: Photocurrent Generation with Two‐Dimensional van der Waals Semiconductors. Issue 30 (July 2015) - Buscema, Michele; Island, Joshua O.; Groenendijk, Dirk J.; Blanter, Sofya I.; Steele, Gary A.; van der Zant, Herre S. J.; Castellanos‐Gomez, Andres
Abstract Review: 221 refs.